MODL-26. Development of humanized immune system, posterior fossa A ependymoma patient-derived xenograft model. (3rd June 2022) - Griesinger, Andrea; Lang, Julie; Donson, Andrew; Grimaldo, Enrique; Pierce, Angela; Knox, Aaron; Steiner, Jenna; Serkova, Natalie; Ritzmann, Timothy; Grundy, Richard; Foreman, Nicholas
Abstract: Cellular interactions between tumor and immune cells are critical in ependymoma biology. We have shown distinct immunobiology phenotypes by ependymoma molecular subgroups, with PFA2 developing an anti-tumor immune phenotype and in contrast PFA1 tumor immune cells being pro-tumor. We recently established two fully characterized pediatric PFA1 intracranial xenograft models in NSG mice. These models, while critical for advancing PFA studies, lack the ability to make lymphocytes. To address this we have established a humanized orthotopic model of PFA1 ependymoma that are grafted to produce functional human lymphocytes. To do this, CD34+ human umbilical cord blood was injected into the cranial facial vein of newborn, irradiation immunodepleted, BRGS mice. Human immune chimerism was determined at 10 weeks by flow cytometry of peripheral blood. Next, we injected existing PDX model MAF-928_XF cells into the 4th ventricle at 12 weeks age and tumors were monitored by MRI. Initial scanning found the tumors were delayed in developing, consistent with other humanized solid tumor mouse models. Mice were euthanized between 32-34 weeks age and necropsies were performed to isolate brain, lymph nodes, blood and spleen. Human chimerism was detectable, by flow cytometry, in spleen, lymph nodes and blood, and most cells were T-cells. Human T-cells were detectable in all tumors, in proportions consistent with human disease (0.05-0.5% of CD45+). Tumors also had 35-50% mouse myeloid infiltration. Tumors were MHC I negative and MHC II positive, and PD-L1 low. Histology was consistent with human ependymoma. We are using spatial proteomics to determine cellular location and phenotype of infiltrating immune cells. Initial studies indicate this model will be usable for modeling the critical tumor-immune interactions and pre-clinically testing the next therapies in PFA ependymoma and can be easily adapted to other pediatric brain tumors in which immune factors have a critical role.